Isolation of Xylanase Producing Strains, Optimization of Fermentation Conditions and Research on Enzymatic Properties - Huilong, Ji; Xin, Gao; Wenxuan, WU; Zhuang, Ma; Qing, Qing (Journal of Biology and Life Science, 2021)
In this study, we successfully isolated a strain of Aspergillus oryzae TR08, which produced xylanase secreted to the outside of the cell productively. The enzyme activity and specific activity in the fermentation broth of this strain reached peak values of 451 IU/mL and 1963 IU/mg after 156 h of fermentation. A single factor experiment was designed, and it was found that the strain was adjusted to the initial pH of the fermentation broth to 7.5 in a shaker at 180 rpm and 32 °C. After 156 h of fermentation, the enzyme activity reached a maximum of 1264 IU/mL. The optimal reaction temperature and pH value of the xylanase were 55 °C and 7.5, respectively, and it had excellent acid and alkali resistance and a wide pH activity range. The xylanase was increased the catalytic activity by 15% in 0.25 mM Fe3+, and the biological activity of the enzyme was not affected in the sodium dodecyl sulfate environment.